Análisis de soluciones artesanales para la caída del cabello de hombres y mujeres en la ciudad de Guayaquil - Bran Pluas, Esther Patricia (2021)
This investigative document was executed in the city of Guayaquil, the same one that aimed to strengthen an orientation of solutions for hair loss of men and women in the city of Guayaquil, including the development of hygienic effects in the application of localized hair types with the utmost respect, and awareness of using chemical-free hair care products. This study was developed to analyze artisan solutions for hair loss in men and women in the city of Guayaquil. When it comes to hair loss, it is the scalp that is most affected, whether temporary or permanent. It is said to cause hair loss: family genetics, persistent nutrition and stress experienced daily, and depression that requires medication and other hair treatments. According to the above, a concern is expressed in people who suffer from this constant hair loss, and it has been proposed to develop hair creams in variable concentrations in order to stimulate hair growth to prevent hair loss. Also improving the condition of the hair and generating a healthier and stronger growth.